Flourishing Scale: Adaptation and Evidence of Validity in a Chilean High School Context - Carmona-Halty, Marcos; Marín-Gutierrez, Mauricio; Mena-Chamorro, Patricio; Sepulveda-Páez, Geraldy; Ferrer-Urbina, Rodrigo (Frontiers in Psychology, 2022)
This study aimed to adapt the Flourishing Scale to a Chilean high school context and provide evidence of its validity. Data were collected from 1348 students (52% girls) from three different Chilean schools. The results of confirmatory factor analysis (CFA) supported a one–factor solution, multiple–group CFA supported gender invariance, and structural equation model indicated that the FS is related to positive and negative academic feelings. Overall, the evidence indicates that the Flourishing Scale adapted to the high school context is an instrument that produces valid and reliable scores in our high school Chilean sample.